Road safety: implications for sustainable development in Latin America - Bezerra, Barbara Stolte [UNESP]; Kaiser, Ilza Machado [UNESP]; Battistelle, Rosane Aparecida Gomes [UNESP] (Inderscience Publishers, 2015)
Road accidents cause more deaths than homicides in Latin America, nevertheless it is not highlighted as a major concern by media and society. World Health Organization put this issue in high priority by releasing the Decade of Action in Road Safety that establishes five pillars to guide national road safety plans and activities. This paper addresses the drawbacks in the implementation of these actions in Latin American countries and its implications to achieve a sustainable development. The main concerns are: lack of empowerment of the road safety management organisations; lower vehicular standards; corruption related to the enforcement of traffic safety laws to and to the construction of safer roads; absence of safety vehicular inspections; vehicle fleet increase, decrease of public transportation demand; and the absence of a safety culture. Without facing these problems, sustainable development in Latin America will be impaired, once road safety is a fundamental link to achieve sustainability.
Keywords: Latin America; Road safety; Sustainable development; Sustainability; Sustainable transport; Road accidents; Empowerment; Safety management; Vehicle standards; Corruption; Law enforcement; Traffic laws; Rconstruction; Safety inspections; Vehicle inspections; Vehicle fleet increase; Public transport demand; Safety culture